2019
DOI: 10.3390/su11123480
|View full text |Cite
|
Sign up to set email alerts
|

What Does It Take to Make the Compact City Liveable for Wider Groups? Identifying Key Neighbourhood and Dwelling Features

Abstract: Compact cities promote sustainability through several mechanisms, and high-density city development has become a key strategy for policy decision makers to accommodate population growth and mitigate human impacts of the local and global environment. The aim of this study is to identify elements of the built environment and inner-city dwellings considered important for improving compact-city liveability for various groups throughout their life cycles. To attend to the depth and complexity of this issue, this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 50 publications
0
23
0
2
Order By: Relevance
“…Hence, lands for a single function or special use should not occupy a significant percentage of the city's land when it is necessary. To fulfil this principle, see Kotulla et al that made the city with wider groups in the urban neighborhoods (Kotulla et al, 2019). (v) Allocating some urban land to build homes for the needy and the homeless.…”
Section: Theories On New Housing and Town Building Policiesmentioning
confidence: 99%
“…Hence, lands for a single function or special use should not occupy a significant percentage of the city's land when it is necessary. To fulfil this principle, see Kotulla et al that made the city with wider groups in the urban neighborhoods (Kotulla et al, 2019). (v) Allocating some urban land to build homes for the needy and the homeless.…”
Section: Theories On New Housing and Town Building Policiesmentioning
confidence: 99%
“…Overall, the cost-effectiveness of these schemes has been questioned (Miller, Wilson and Wood, 2020 [74]) (Van Wee et al, 2011 [75]) (ITF-OECD, 2011 [76]), and in some cases it has been shown that these may have adverse consequences (IEA, 2020 [77]). For instance, in some cases, these schemes have even prompted net increases in CO2 emissions (Klößner and Pfeifer, 2015 [78]) and regressive effects have also been found (Busse et al, 2012 [79]). This should all be taken into account.…”
Section: Decoupling-type Recovery Measures: Stimulating Cleaner Car Omentioning
confidence: 99%
“…With growing recognition that relocation requires more than housing, communal infrastructure (e.g., schools and hospitals) have accompanied recent projects [24]. Additionally, quality of high-density living can be improved by access to local supply, such as markets and stores where residents can purchase everyday needs and avoid burdensome trips for small necessities [25]. In this study, built livability is assessed as a composite of infrastructure, housing, and accessible services.…”
Section: Identifying and Measuring Livable Relocation Communitiesmentioning
confidence: 99%